NiOx nanoparticles obtained from hydrothermally treated NiC2O4 as an electron blocking layer for organic photodetectors. (29th September 2020) - Li, Yi; Mao, Longmei; Yu, Longxin; Li, Xifeng; Zhang, Jianhua
Abstract: A room-temperature p-type NiOx film synthesized from a NiC2 O4 precursor via hydrothermal treatment is employed as an electron blocking layer (EBL) to fabricate organic photodetectors (OPDs). A simple and efficient calcine process at 375 °C in air decomposes the NiC2 O4 particles into NiOx, removes organic components and crystal water, and releases CO2 gas. Our experimental results indicate that this gaseous by-product prevents the agglomeration of NiOx, which yields smaller nanoparticles (5–10 nm). The formation of an EBL at room temperature improves device performance. After optimization, the performance parameters obtained, including dark current density, responsivity, specific detectivity and response, are 1.13 × 10 −7 A cm −2, 0.74 A W −1, 3.86 × 10 12 Jones, and 0.5/8 ms, respectively. Additionally, the dark current is reduced by more than an order of magnitude after the insertion of the NiOx layer. The proposed simple and easy method for producing an EBL could be beneficial for the commercial low-temperature and large-area preparation of OPDs.